A patent review of IDO1 inhibitors for cancer. (3rd April 2018) - Cheong, Jae Eun; Ekkati, Anil; Sun, Lijun
ABSTRACT: Introduction : Indoleamine 2, 3-dioxygenase 1 (IDO1) is overexpressed by cancer cells and the antigen presenting dendritic cells in the tumor microenvironment (TME). Activation of IDO1 depletes tryptophan and produces kynurenine, which induces T cell anergy and suppresses tumor control by the immune system. When combined with an immune checkpoint inhibitor, IDO1 inhibitors have shown promising anticancer activity in preclinical tumor models as well as in early stage clinical trials. Areas covered : IDO1 inhibitors disclosed in the patent literature from 2013-2017 are categorized, when applicable, according to their structural similarity to the clinical development candidates indoximod and PF-06840003, navoximod, epacadostat, KHK2455 and aryl-1, 2-diamines, and BMS-986205 among others, respectively. Representative structures and their IDO1 inhibitory activity are presented to highlight the novelty and activity. Finally, the reported cocrystal structures were analyzed to provide insights for inhibitor-enzyme interactions and guidance for the design and discovery of next generation inhibitors. Expert opinion : This review demonstrates that the structural diversity of new IDO1 inhibitors could be expanded via a number of approaches.